2003
DOI: 10.1021/jp0346099
|View full text |Cite
|
Sign up to set email alerts
|

14,15N NMR Shielding Constants from Density Functional Theory

Abstract: The prediction of nuclear magnetic resonance (NMR) shielding parameters for the N atom represents a particularly difficult task for most of the Hartree-Fock (HF)-based or density functional theory (DFT)-based methodologies. In fact, for some molecular systems, the effect of the presence of a lone pair and multiple bonds on the N atom makes the use of higher correlated methods absolutely necessary to obtain accurate results. In this article, we present an extensive study covering almost the entire spectrum of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
(183 reference statements)
2
17
0
Order By: Relevance
“…We also include backbone nitrogen NMR shielding constant RMSDs in Table , because they have some importance in protein structure determination. They show much larger RMSDs (>4 ppm for all models) than what was obtained for carbon, but this is not unexpected, since the large variations observed for nitrogen are dependent more heavily on the level of electronic structure theory . Chemical shifts of N atoms also generally exhibits a larger span than C atoms in protein structures…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…We also include backbone nitrogen NMR shielding constant RMSDs in Table , because they have some importance in protein structure determination. They show much larger RMSDs (>4 ppm for all models) than what was obtained for carbon, but this is not unexpected, since the large variations observed for nitrogen are dependent more heavily on the level of electronic structure theory . Chemical shifts of N atoms also generally exhibits a larger span than C atoms in protein structures…”
Section: Resultsmentioning
confidence: 58%
“…They show much larger RMSDs (>4 ppm for all models) than what was obtained for carbon, but this is not unexpected, since the large variations observed for nitrogen are dependent more heavily on the level of electronic structure theory. 80 Chemical shifts of N atoms also generally exhibits a larger span than C atoms in protein structures. 81 Based on the above analysis, we conclude that, for the purpose of computing NMR shielding constants of 13 C, model 2 is sufficiently accurate.…”
Section: Resultsmentioning
confidence: 99%
“…Recently Leniak and J. Jaźwiński, showed that the non‐relativistic B3PW91/[6‐311++G(2d,p), Stuttgart] computational protocol reproduced the 15 N NMR parameters as good as the more expensive relativistic CGA‐PBE//QZ4P ZORA approaches for a set of model complexes of rhodium(II) tetraformate with nine nitrogenous organic ligands. Fadda et al calculated the shielding constant of 132 different N atoms covering almost the entire spectrum of nitrogen shielding, from +400 to –50 ppm employing the non‐relativistic sum‐over‐states density functional perturbation theory (SOS‐DFPT) and assessed the potential of the SOS‐DFPT local approximations through the comparison of N atoms that belong to similar molecular systems to experimental data.…”
Section: Experimental Section and Computational Detailsmentioning
confidence: 99%
“…In particular, density functional theory (DFT) is a useful tool to calculate both 14 N quadrupolar and chemical shift NMR tensors, as reported in the literature for several solid materials. [31][32][33][34][35][36][37] Herein, we report an original study of diheptylazobenzene (7AB) [38,39] in its nematic and smectic A phases (see Figure 1), based on a combined approach between experimental 14 N and 2 H NMR and DFT ab initio calculations. Previous studies on the 7AB mesogen, based on the sole 2 H NMR study of 7AB selectively deuterated in the aromatic core and/or in the alphamethyl position, [40][41][42][43] are limited to the determination of the main orientational order parameter, S zz , and to studying the impact of UV illumination on both molecular configurational changes and average S zz values.…”
Section: Introductionmentioning
confidence: 99%